2014
DOI: 10.1007/s13760-014-0311-1
|View full text |Cite
|
Sign up to set email alerts
|

ADC evaluation of the corticospinal tract in multiple sclerosis

Abstract: Apparent diffusion coefficient (ADC) values derived from diffusion-weighted MR imaging (DWI) provide important information about tissues. The goal of this study was to evaluate the ADC values in the corticospinal tract regions in multiple sclerosis (MS). The ADC values of 42 patients with multiple sclerosis and 46 healthy people were measured. The ADC values in the corticospinal tract at the capsula interna posterior crus from six points and mesencephalon from three points bilaterally in MS patients were compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 14 publications
2
11
1
Order By: Relevance
“…It has been reported that some patients with multiple sclerosis or mild encephalitis/encephalopathy with reversible splenial lesions showed hyperintensity on DWI and decreased ADC values-this was true in our case ( 14 , 15 ). The mechanisms underlying the transient reduction of diffusion in patients with these inflammatory diseases may be related to intramyelinic edema, interstitial edema, and the infiltration of inflammatory cells ( 14 , 16 ). Thus, the DWI and ADC abnormalities may be related to these mechanisms.…”
Section: Discussionsupporting
confidence: 73%
“…It has been reported that some patients with multiple sclerosis or mild encephalitis/encephalopathy with reversible splenial lesions showed hyperintensity on DWI and decreased ADC values-this was true in our case ( 14 , 15 ). The mechanisms underlying the transient reduction of diffusion in patients with these inflammatory diseases may be related to intramyelinic edema, interstitial edema, and the infiltration of inflammatory cells ( 14 , 16 ). Thus, the DWI and ADC abnormalities may be related to these mechanisms.…”
Section: Discussionsupporting
confidence: 73%
“…Of these sites, the optic nerve is the best described, because inflammatory demyelinating optic neuritis may be the initial presenting feature in patients with MS [5,6]. Conventional and non-conventional magnetic resonance imaging (MRI) techniques, such as diffusion tensor imaging, diffusion-weighted imaging, and magnetization transfer imaging are used for the diagnosis of optic neuritis [7][8][9][10][11]. However, MRI examinations are time consuming, expensive, less available and often require the use of gadolinium contrast.…”
Section: Introductionmentioning
confidence: 99%
“…In MS, the diffusion MRI has been used to investigate differences between various types of lesions 7 or lesions and normal appearing white matter (NAWM), 8 between MS patients and healthy controls, 9,10 as well as to study diffusion parameters in relation to clinical measures. [10][11][12] However, the results of DWI and DTI studies in relation to neurological disability in MS are not consistent.…”
Section: Restriction Spectrum Imaging Of White Matter and Its Relatiomentioning
confidence: 99%